Acoustic emission monitoring of damage progression in Glass/Epoxy composites during static and fatigue tensile tests. (March 2018) - Roundi, Walid; El Mahi, Abderrahim; El Gharad, Abdellah; Rebiere, Jean-Luc
Abstract: In this paper, static and fatigue behavior of Glass/Epoxy composite laminates are investigated. During experimental tests the gradual degradation and damage evolution in the composites tested were monitored using the acoustic emission method ( AE ). The specimens tested were made with different stacking sequences ([02 /902 ]s, [902 /02 ]s, [03 /90]s and [903 /0]s ) according to the vacuum infusion procedure. The analysis and observation of AE signals collected during experimental tests allow the identification of the various damage mechanisms, and detect those which are the most critical, leading to the failure of the tested specimens. The accumulated damage is manifested by matrix cracking, inter-ply debonding, delamination and fiber breakage. The acoustic signals collected during the tests were analyzed by a classification method which consists of the k -means method and principal component analysis ( PCA ). The results of the acoustic emission signals accumulated during static and fatigue tests are compared in order to assess and evaluate the intensity of these activities for each stacking sequence. The distribution of amplitude and the time dependency of the different damage modes are shown in this study.